Distance between midline and vertebral artery groove of atlas – a real aid to the neurosurgeon - Mukesh S,; Prabhat G,; Mohd Salahuddin A,; Kumar SR, (Department of Surgery, UKM Medical Centre, 2014)
The knowledge of the relationship of the vertebral artery with the atlas is very important, in order to avoid any injury to the vertebral artery, during surgeries in the craniovertebral region. Different researchers have measured the distance of the vertebral artery from the midline along the posterior arch of atlas (oblique distance), but some authors have measured the perpendicular distance of vertebral artery from the midline. Usually, it is the perpendicular distance along which the surgeons are exploring in this region. Hence, the present study was planned to study and compare both oblique and perpendicular distances of the vertebral artery from the midline and find out statistical differences between these two parameters. It was carried out on 30 atlas vertebrae of Indian origin. The oblique and perpendicular distances of vertebral artery groove from midline and the thickness of vertebral artery groove were measured. The results suggest that dissection on the posterior aspect of the arch of atlas should remain 17.00 mm lateral to the midline and dissection on the superior aspect of the arch of atlas should remain 8.00 mm from the midline to prevent injury to the vertebral artery. It was also observed that “oblique distances of vertebral artery groove from the midline to the medial margin of inner and outer cortex are larger than the corresponding perpendicular distances from the midline”. Although, the differences of oblique and perpendicular distances are not statistically significant but it may be clinically significant for the surgeons operating in the craniovertebral region. Hence, it is concluded that the surgeon should be aware of both the distances while operating in the craniovertebral region to avoid any iatrogenic injury to the vertebral artery.